Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.3347/kjp.2008.46.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Lupoid Cutaneous Leishmaniasis with Glucantime and Topical Trichloroacetic Acid (A Case Report)

Abstract: Lupoid leishmaniasis is a unique form of cutaneous leishmaniasis characterized by unusual clinical features and a chronic relapsing course, mostly caused by infection with Leishmania tropica. In this clinical form, 1-2 yr after healing of the acute lesion, new papules and nodules appear at the margin of the remaining scar. Herein, we describe a case of this clinical form that was resistant to 2 courses of treatments: systemic glucantime and then a combination therapy with allopurinol and systemic glucantime. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Others have also demonstrated the benefits of sequential combined administration of allopurinol and benznidazole in human chronic disease, which leads to changes in T and B immune responses indicative of beneficial therapeutic outcomes (29). Similarly, an improvement in the treatment of cutaneous leishmaniasis also has been observed when allopurinol was given in combination with antimony compounds (30, 31) or trichloroacetic acid (32). Rial et al (33) evaluated the effect of the allopurinol combined with benznidazole in C3H/HeN and C57BL/6J mice with T.…”
Section: Introductionmentioning
confidence: 86%
“…Others have also demonstrated the benefits of sequential combined administration of allopurinol and benznidazole in human chronic disease, which leads to changes in T and B immune responses indicative of beneficial therapeutic outcomes (29). Similarly, an improvement in the treatment of cutaneous leishmaniasis also has been observed when allopurinol was given in combination with antimony compounds (30, 31) or trichloroacetic acid (32). Rial et al (33) evaluated the effect of the allopurinol combined with benznidazole in C3H/HeN and C57BL/6J mice with T.…”
Section: Introductionmentioning
confidence: 86%
“…13 They reported 13 Nilforoushzadeh and colleagues evaluated intralesional MA and TCA in the treatment of patients with acute CL. 14 They found that after 6 weeks, 68% and 65.7% of patients in the TCA and MA groups, respectively, experienced complete clinical cure.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several physical therapeutic methods are available, including CO 2 laser, cryotherapy, thermotherapy, and trichloroacetic acid (TCA). [9][10][11][12][13][14] Accordingly, consideration of new local treatment methods with fewer side effects is preferred. TCA is a caustic and hemostatic material.…”
mentioning
confidence: 99%
“…A lupoid leishmaniasis, a particular form of cutaneous Leishmania infection, common in the Middle East and Afghanistan, mainly caused by Leishmania tropica , and typically resistant to the common therapies, was excluded thanks to the histological findings (3).…”
Section: Case Reportmentioning
confidence: 99%